PERSEPSI KESESUAIAN MATERI KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA STMIK STIKOM INDONESIA - Paramitha, Dana; Nilawati, Utami (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
STMIK STIKOM Indonesia as an information technology-based higher education institution organizes entrepreneurship courses for students to inspire and motivate entrepreneurship. This course is compulsory for students who are already in their seventh semester. From initial interviews with several students who have attended entrepreneurship courses about the material given in class, it was revealed that it is necessary to provide additional time and relevant material for the implementation of entrepreneurial concepts and practices on campus. Related to this, the researcher tries to further examine through this research to dig deeper into students' perceptions about entrepreneurship lecture materials provided by lecturers who are teaching courses so far which will later be used as material for evaluating the next semester's learning plan, as well as trying to find out to what extent the effectiveness of education entrepreneurship on the STMIK STIKOM Indonesia campus and its impact on students' interest in entrepreneurship both during their time as students and after graduation.